ANALISIS FAKTOR-FAKTOR PENGHAMBAT PEMBENTUKAN TEFA PADA KONSENTRASI KEAHLIAN DESAIN, PEMODELAN DAN INFORMASI BANGUNAN UNTUK MENINGKATKAN CAPAIAN KERJA MAHASISWA DI SMKN 4 PALEMBANG - Sahera Silvia Vaesar; Hasan Maksum; Dony Novaliendry (Ensiklopedia of Journal, 2025)
Teaching Factory (TEFA) is a production-based learning model that integrates industry competencies into the learning process in vocational schools. This study aims to analyze the inhibiting factors for establishing a Teaching Factory in the Design Modeling and Building Information (DPIB) expertise concentration at SMKN 4 Palembang. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. Research subjects included the Head of DPIB Expertise Concentration, 8 productive teachers, 1 toolman, and school policy documents. The results show five main categories of inhibiting factors: (1) Technical constraints in the form of limited quantities and adequate computer specifications for BIM applications, as well as limited industrial software licenses; (2) HR constraints with teacher competencies who have not mastered integrated BIM workflows and limited numbers of certified construction teachers; (3) Managerial constraints include the lack of a TEFA Core Team and difficulties in integrating learning schedules with TEFA projects; (4) Financial constraints with an initial investment budget gap of IDR 300,000,000 exceeding routine school fund allocations; (5) Industry collaboration constraints in the form of difficulties in building consistent formal partnerships for TEFA projects. This study recommends establishing a TEFA Core Team, improving teacher competence through BIM training, applying for funding through the SMK PK program or corporate CSR, and strengthening partnerships with local consultants and contractors. Keywords: Teaching Factory, DPIB, Vocational School, Inhibiting Factors, BIM.